2015
DOI: 10.1097/yco.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Patient personality and therapist countertransference

Abstract: In the last years, several studies have empirically demonstrated the presence of a specific pattern of therapist responses that are related to different patient personality disorders. Other works showed how the effects of the therapist's technique depend on the emotional context in which they are delivered and in particular countertransference experiences. Moreover, researchers suggest that the therapist's emotional responses occur across all kinds of therapy and are independent of the therapist's theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 40 publications
3
33
0
3
Order By: Relevance
“…Our findings support the view that therapists' emotional reactions to their patients may be an important factor in psychotherapy [10]. Patient characteristics, technique, and therapist reactions interact; therefore, evaluation of anyone of these in isolation from the others may provide an incomplete understanding of their role in relation to outcome.…”
Section: Figsupporting
confidence: 56%
“…Our findings support the view that therapists' emotional reactions to their patients may be an important factor in psychotherapy [10]. Patient characteristics, technique, and therapist reactions interact; therefore, evaluation of anyone of these in isolation from the others may provide an incomplete understanding of their role in relation to outcome.…”
Section: Figsupporting
confidence: 56%
“…use the term "emotional reaction" interchangeably with "emotional response" and "countertransference") can play a crucial role in psychotherapy, regardless of therapeutic orientation and across different forms of psychopathology (Hayes et al, 2011;Colli and Ferri, 2015).…”
mentioning
confidence: 99%
“…The avoidant PD criteria showed a weak, but not significant, positive correlation with a Confident response. Previous empirical studies have reported that Confident is the most significant response from the group in question (16). However, this result might also reflect that the avoidant patients are a more heterogeneous patient group.…”
Section: Discussionmentioning
confidence: 82%
“…One of the benefits of using questionnaires is their quantitative nature; they can be distributed to many therapists, and one can subsequently receive large amounts of experienced feelings that can be used to identify common patterns of feelings (18). The Feeling Word Checklist (FWC) (10,14,15), in various versions, is one of the most used questionnaires for research on CT (16).…”
mentioning
confidence: 99%